Prevalence and molecular characterization of giardia duodenalis in lambs in hakkari̇ region - AKYILDIZ, GÜRKAN (My University, 2022)
Giardia duodenalis is a single-celled, flagellated protozoan parasite that lives in the intestines of various mammals, including humans. Infection is transmitted by ingestion of contaminated faeces, contaminated water, and food containing Giardia cysts. In this study, it was aimed to determine the prevalence and molecular characterization of Giardia duodenalis in lambs in Hakkari Region. he animal material of the study consists of 200 lambs in the Hakkari region. Stool samples were collected from the rectum of lambs with disposable latex gloves. Stool samples were first examined microscopically for Giardia duodenalis cysts by nativeLugol staining method. DNA was then extracted from all 200 samples. Then, Nested PCR was performed with appropriate primers. After that, PCR products were run in agarose gel and images were obtained on a gel imaging device. Then the positive PCR products were sent to the sequence bidirectionally. Then, the sequence results were blasted and alligned and compared with the relevant reference genes in the GenBank. As a result of microscopic examination, Giardia duodenalis cysts were found in 34 (%17) of 200 samples. As a result of Nested PCR, positivity was detected in 37 (%18.5) of 200 samples. Assemblage E detected as a result of sequencing. As a result, it was concluded that Giardia duodenalis is intensively observed in lambs in the Hakkari region.
Keywords: Giardia duodenalis; Hakkari; Lamb; Molecular